The effect of cognitive strategy instruction enriched with active learning techniques on word problem-solving skills of students with learning disabilities. - Filiz, Tunahan (Humanities & Social Sciences Communications, 2026)
This study aimed to investigate the effectiveness of cognitive strategy instruction (CSI) enriched with active learning (AL) techniques in teaching word problem solving to primary school students with learning disabilities, as well as to examine the overall instructional process. Word problem solving is the process of using contextual information from real-life or fictional situations to develop mathematical solutions. The research was designed with an embedded mixed-method model. The quantitative phase included 30 third-grade students with learning disabilities, while the qualitative phase involved six randomly selected students from the experimental group. Quantitative analyses revealed that students in the experimental group showed significantly higher achievement in problem-solving tests, indicating the positive impact of CSI enriched with AL techniques. Qualitative findings highlighted increased class participation, enhanced collaboration, and more positive attitudes toward mathematics. Furthermore, teacher and peer interactions supported the problem-solving process, and the use of tools promoting mathematical thinking strengthened performance. The results demonstrated that CSI enriched with AL techniques encouraged strategic thinking and the generation of alternative solutions in word problem solving. The study, limited to three learning outcomes within the third-grade mathematics curriculum in Turkey, suggests that teachers should adapt and implement such instructional approaches across other mathematical domains, given the students’ positive experiences and outcomes.